2022
DOI: 10.3390/jcm11133782
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Inflammatory Cytokine Profile in Obesity-Associated Asthma: Effects of Weight Loss

Abstract: Obesity and asthma are associated with systemic inflammation maintained by mediators released by adipose tissue and lung. This study investigated the inflammatory serum mediator profile in obese subjects (O) (n = 35), non-obese asthma (NOA) patients (n = 14), obese asthmatics (OA) (n = 21) and healthy controls (HC) (n = 33). The effect of weight loss after bariatric surgery (BS) was examined in 10 OA and 31 O subjects. We analyzed serum markers including leptin, adiponectin, TGF-β1, TNFR2, MCP-1, ezrin, YKL-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 116 publications
0
19
0
Order By: Relevance
“…Among these studies, high leptin was identified frequently in patients with asthma [ 72 , 86 , 87 , 88 , 89 ]. Some studies have reported inverse correlations between leptin and lung function [ 88 , 90 , 91 , 92 ] as well as weight loss [ 88 , 91 , 93 ]. There were positive associations between leptin and symptomatic atopy [ 89 ] and BMI [ 86 , 94 ].…”
Section: Leptin and Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, high leptin was identified frequently in patients with asthma [ 72 , 86 , 87 , 88 , 89 ]. Some studies have reported inverse correlations between leptin and lung function [ 88 , 90 , 91 , 92 ] as well as weight loss [ 88 , 91 , 93 ]. There were positive associations between leptin and symptomatic atopy [ 89 ] and BMI [ 86 , 94 ].…”
Section: Leptin and Asthmamentioning
confidence: 99%
“…The cross-sectional studies manifested some findings, from high levels of leptin in overweight patients with asthma compared to normal weight patients with asthma or in asthma patients of obese compared to non-obese asthma patients [ 86 ] to high levels of leptin related to BMI and severe lung function [ 86 , 88 , 90 , 94 ]. While some studies revealed no differences in leptin between overweight patients with asthma and without asthma [ 94 ] or no differences between leptin and lung function or BMI [ 93 , 95 , 96 ].…”
Section: Leptin and Asthmamentioning
confidence: 99%
“…Some of the studies included in this meta-analysis involved pulmonary function tests, such as an FEV in one second (FEV1) and FVC/FEV1 ratio, and their correlation with leptin levels or severity of asthma. Leptin was shown to be inversely correlated with both FEV1, FVC/FEV1 ratio [29,31,33,36], and FEV1/FVC ratio [35], which may suggest that nonatopic inflammation (including not only leptin, but also other adipokines such as adiponectin) increase the severity of asthma by obesity-dependent and independent mechanisms [52,53]. In addition, serum leptin levels were associated with maximum decreases in FEV1 after exercise [25], and increased the odds of an abnormal FEV1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in individuals with obesity and insulin resistance, a significant correlation was revealed between the expression of TGF-β1 and the presence of various collagen types, including collagen type I, III, and VI, which was further associated with the extent of fibrosis within white adipose tissue ( 242 ). Although the role of TGF-β1 in the context of obesity-induced airway fibrosis in asthma remains elusive, and one study observed no difference in serum levels of TGF-β1 between individuals with asthma and obesity compared to healthy controls ( 243 ), the role of TGF-β1 in the context of obesity-induced airway fibrosis should be considered.…”
Section: The Association Between Asthma Obesity and Alterations In Ai...mentioning
confidence: 99%